α -L-Rhamnosidase and β -D-glucosidase activities in fungal strains isolated from alkaline soils and their potential in naringin hydrolysis - Eliades, Lorena Alejandra (2011)
α -L-Rhamnosidases (EC 3.2.1.40) and β -D-glucosidases (EC 3.2.1.21) obtained from several microbial sources are potential catalysts in food, beverage, and pharmaceutical industries. However, the enzyme preparations currently used have limitations related to the stability and activity of the enzyme as well to their reuse. A microtiter screening was carried out in 55 fungal strains isolated from alkaline soils, to obtain active α -L-rhamnosidases and β -D-glucosidases at pH 9.0. While α -L-rhamnosidase activity was detected in 45% of the strains tested, β -D-glucosidase activity was found only in 27%. Based on the fungal ability to produce α -L-rhamnosidase activity, cultures were supplemented with naringin to study the activities of the enzymes and the potential of the fungal strains on naringin hydrolysis. About 70% of the fungal strains tested increased the activities of both enzymes in the naringin-supplemented cultures as compared to non-supplemented ones. This effect was higher in Acrostalagmus luteo-albus LPSC 427 (15.3 fold) for α -L-rhamnosidase activity and Metarrhizium anisopliae LPSC 996 (51.1 fold) for β -D-glucosidase activity. All the enzyme preparations tested hydrolyzed naringin at pH 9.0, being that obtained from Acremonium murorun LPSC 927 cultures the one which showed highest hydrolysis. Here, different fungal species are reported for the first time for their ability to produce α -L-rhamnosidase and β -D-glucosidase activity at alkaline pH.